Vocational education and training in Hungary : ReferNet country report 2008 - Bükki, Eszter [Verfasser]; Köpeczi-Bócz, Tamás [Herausgeber] (Observatory for Education Development, 2009)
The ReferNet network established by Cedefop prepare the annually updated ReferNet country Reports formerly Thematic Overview which discuss the national vocational education and training systems, structured around the most important aspects of the subject. This Report provides information on Hungary´s Policy Context and its Framework of VET as well as information about IVET and CVET, Teachers and Trainers, skills and competence development and financing. The final chapter provides an outlook of the Impact of Europeanisation on education and training. (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.5.2 Berufliche Weiterbildung; S 1.3 Berufliche Erstausbildung; I 2.2.2 Osteuropa; Berufsbildung; Berufsausbildung; Berufliche Weiterbildung; Bildungsfinanzierung; Bildungspersonal; Ungarn